Physicochemical, microstructure and antioxidant properties of microalgae-derived fucoxanthin rich microcapsules - Su, Chern Foo; Khong, Nicholas Mun Hoe; Md. Yusoff, Fatimah (Elsevier, 2020)
The conjugated double bonds in carotenoids confer antioxidant activities but also makes it unstable. The purpose of this study was to preserve the antioxidant activity of fucoxanthin rich fraction extracted from the microalgae, Chaetoceros calcitrans, via microencapsulation. The effect of selected microencapsulation parameters i.e., drying process, total solid content, type of carrier agent and emulsifier to the physicochemical, microstructure and antioxidant properties of the resulting microcapsule, were investigated. When compared to spray-dried microcapsules, the freeze-dried microcapsules showed better carotenoid preservation and antioxidant activities. Nevertheless, both spray-dried and freeze-dried microcapsules reported water solubility index, moisture, and water activity well within food powder recommended values. Among the formulations, formulation with 40% carrier agent at 1:1 maltodextrin: gum Arabic and 1% w/w Tween 20 emulsifier successfully microencapsulated fucoxanthin with the highest carotenoid and antioxidant activities (p < 0.05), both in freeze-dried and spray-dried microcapsules. This study found that the produced fucoxanthin microcapsule showed good bioactivity retainment leading to wider application possibilities where the microencapsulation formulation could prove useful for other carotenoids too.